2014
DOI: 10.1111/dewb.12054
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Quality of Informed Refusal Process: A Cross‐Sectional Study from Iranian Patients' Perspectives

Abstract: Patients have the right to refuse their treatment; however, this refusal should be informed. We evaluated the quality of the informed refusal process in Iranian hospitals from patients' viewpoints. To this end, we developed a questionnaire that covered four key aspects of the informed refusal process including; information disclosure, voluntariness, comprehension, and provider-patient relationship. A total of 284 patients who refused their treatment from 12 teaching hospitals in the Isfahan Province, Iran, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
8
1
Order By: Relevance
“…Failure to observe this right has been consistently reported by several studies in Iran. 31,36,37 It is the patients’ right to refuse a treatment 9 and the medical team is required to provide enough information to patients and enable them to make a proper decision. As indicated by other studies, participation of the nurses in this regard helps the patients to make more informed decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to observe this right has been consistently reported by several studies in Iran. 31,36,37 It is the patients’ right to refuse a treatment 9 and the medical team is required to provide enough information to patients and enable them to make a proper decision. As indicated by other studies, participation of the nurses in this regard helps the patients to make more informed decisions.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by other studies, participation of the nurses in this regard helps the patients to make more informed decisions. 9,10 Therefore, it is recommended that nurses help physicians in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Informed consent is effective only when patients have sufficient information about different treatment options (Faghanipour, Joolaee, and Sobhani 2014). Studies show that in some cases although patients long to be informed, they do not receive adequate information about their surgical procedure (Farzandipour, Sheikhtaheri, and Sadeqi Jabali 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, where education standards and literacy levels are comparably lower, information asymmetries are often observed between patients and healthcare professionals [15,16]. Moreover, studies conducted in Iran revealed that patients receive limited information about their medical condition and various treatment plans [2,17,18]. A study in this country indicated that 84.4%, 87.4%, and 86% of patients were not informed about other treatment options, bene ts of other treatment options, and complications of other treatment plans, respectively [18].…”
Section: Introductionmentioning
confidence: 99%